Validation of the doubly labeled water method using off-axis integrated cavity output spectroscopy and isotope ratio mass spectrometry - Melanson, Edward L. (Am J Physiol Endocrinol Metab, 2018)
When the doubly labeled water (DLW) method is used to measure total daily energy expenditure (TDEE), isotope measurements are typically performed using isotope ratio mass spectrometry (IRMS). New technologies, such as off-axis integrated cavity output spectroscopy (OA-ICOS) provide comparable isotopic measurements of standard waters and human urine samples, but the accuracy of carbon dioxide production (V̇co(2)) determined with OA-ICOS has not been demonstrated. We compared simultaneous measurement V̇co(2) obtained using whole-room indirect calorimetry (IC) with DLW-based measurements from IRMS and OA-ICOS. Seventeen subjects (10 female; 22 to 63 yr) were studied for 7 consecutive days in the IC. Subjects consumed a dose of 0.25 g H(2)(18)O (98% APE) and 0.14 g (2)H(2)O (99.8% APE) per kilogram of total body water, and urine samples were obtained on days 1 and 8 to measure average daily V̇co(2) using OA-ICOS and IRMS. V̇co(2) was calculated using both the plateau and intercept methods. There were no differences in V̇co(2) measured by OA-ICOS or IRMS compared with IC when the plateau method was used. When the intercept method was used, V̇co(2) using OA-ICOS did not differ from IC, but V̇co(2) measured using IRMS was significantly lower than IC. Accuracy (~1–5%), precision (~8%), intraclass correlation coefficients (R = 0.87–90), and root mean squared error (30–40 liters/day) of V̇co(2) measured by OA-ICOS and IRMS were similar. Both OA-ICOS and IRMS produced measurements of V̇co(2) with comparable accuracy and precision compared with IC.